Multipliers in semihoops - Ting Qian; Wei Wang; Mei Wang (IJRDO -JOURNAL OF MATHEMATICS, 2019)
Semihoops play an important role in the study of fuzzy logic based on left continuous t-norms. In this paper, we introduce the notion of multipliers in semihoops and investigate some related properties of them. Also, we discuss the relations between multipliers and closure operators in semihoops. Moreover, we focus on algebraic structures of the set IM(L) of all implicative multipliers in semihoops and obtain that IM(L) forms a Heyting algebra, when L is an MT L-algebra.